Rezension von: Ruperto-Carola Bd. 37, 38, 39, 40 - Wunder, Gerd (Württembergisch Franken, 1967)
Ruperto-Carola. Band 37 (1965), 364 S. — Band 38 (1965), 396 S. — Band 39 (1966), 448 S. — Band 40 (1966), 528 S. Heidelberg